Hypersensitivity pneumonitis and its correlation with ambient air pollution in urban India. Issue 2 (31st January 2019) - Singh, Sheetu; Collins, Bridget F.; Bairwa, Mohan; Joshi, Jyotsna M.; Talwar, Deepak; Singh, Nishtha; Samaria, Jai K.; Mangal, Daya K.; Singh, Virendra; Raghu, Ganesh
Hypersensitivity pneumonitis (HP) is an immune-mediated lung disease (ILD) caused by sensitisation to inhaled organic antigens or low molecular weight chemical compounds. Recently, there has been increased awareness of environmental factors associated with HP [1]. It has been postulated that when genetically susceptible individuals ("first hit") are exposed to an inciting antigen ("second hit") they develop HP [2]. The first hit is essential, as not all who are exposed to an inciting antigen develop disease. The second hit or the inciting antigen may be bacterial, protozoal, animal or insect protein, or rarely a chemical compound. Certain viral infections and high pesticide exposures may be risk factors for development of HP, perhaps by making the lung more susceptible to organic antigen exposure (facilitating a second hit) [3, 4]. A higher proportion of patients diagnosed with hypersensitivity pneumonitis lives in cities with higher levels of air pollutants. Further studies are warranted to investigate the significance of the association of air pollution to possible causality of HP. http://ow.ly/zH3U30mtocl